GG and the City: What Canada’s Major Translation Award Reveals about Its Metropolises - Legault-Beauregard, Myriam (Text Matters: A Journal of Literature, Theory and Culture, 2025)
In this article I consider the predominance of metropolises in the Canadian publishing sector through the lens of award-winning translations. My research is based on a database of information on Canadian literary prizes (gathered through reports and websites of Canadian prize-granting organisations and Aurora, the Library and Archives Canada catalogue which also queries the WorldCat search engine), specifically on the awardees and finalists of the Governor General’s Literary Awards (GG) in both Translation categories (English-to-French and French-to-English). Data about the cities and publishers connected with the original books and the translations, as well as about the finalist translators’ places of residence, demonstrate that Montréal occupies a central place in this landscape. Indeed, an overwhelming majority (82%) of the finalists in the GG English-to-French Translation category were published in this city; likewise, an appreciable number of books translated from French into English (21% of the finalists in this category, versus 54% for Toronto and 16% for Vancouver). While it is hardly surprising that Toronto and Montréal are, respectively, home to most English and French original publications, Montréal stands out as the main city where translators, in both language combinations, live and work.